VoIP Internet linking for radio amateurs - Taylor, Jonathan (ARRL - the National Association for Amateur Radio, 2009)
Guide to several of the most widely-used VoIP systems used by hams, with particular attention to EchoLink and the Internet Radio Linking Project, or IRLP. The book is designed for beginners who need more information on how to get started, set-up, and use these systems. For the more advanced, it provides plenty of technical "meat" for those who want to dig deeper into VoIP applications and discover how they actually work.--Book cover